Introducing semiotics - Cobley, Paul.; Jansz, Litza ([S.l.] : Totem Books, 2001)
Why study signs? This perennial question of philosophy is answered by the science of semiotics. An animal's cry, poetry, the medical symptom, media messages, language disorders, architecture, marketing, body language - all these, and more, fall within the sphere of semiotics. This book outlines the development of sign study from its classical precursors to contemporary post-structuralism. It identifies the key semioticians and their work and explains the simple concepts behind difficult terms. For anybody who wishes to know why signs are crucial to human existence and how we can begin to study systems of signification, this book is the place to start.
Keywords: Semiotics